Status Gizi, Stimulasi Dan Perkembangan Motorik Halus: Studi Korelasi Pada Anak Usia Dini - Sylvi Harmiardillah; Aisyah Harnina Samantha; Fauziah Amelia Rizky (Jurnal Keperawatan Muhammadiyah, 2026)
Background: Nutritional condition and parental stimulation play a crucial role in early childhood development. Emerging evidence strengthens the view that inadequate nutrition, compounded by a lack of parental stimulation, is a major barrier to the development of fine motor skills in children. This relationship requires further investigation. Objective: This study aims to determine the relationship between nutritional status and parental stimulation and fine motor development in children aged 4–6 years. Methods: This study used an analytic correlation design with a cross-sectional approach. The sample consisted of 32 children and their parents, selected using a total sampling technique. Data were collected through questionnaires and analyzed using the Spearman Rho test with a significance level of p<0.05. Results: The results showed a significant relationship between nutritional status (p=0.000; rs=0.596) and parental stimulation (p=0.000; rs=0.654) and fine motor development. Conclusion: Adequate nutrition provides the biochemical foundation for the maturation of the neuromotor system, while Parental stimulation, through object manipulation and guided play, generates critical sensorimotor feedback that strengthens the neural circuits responsible, which is the basis of proficient fine motor performance. These results demonstrate the importance of parental attention to ensuring adequate nutrition and providing appropriate stimulation to support optimal child development based on age.